First record of the Japanese land snail Ovachlamys fulgens (Gude, 1900) (Gastropoda, Helicarionidae) in Brazil - Teixeira, Larissa [UNESP]; Cunha, Carlo M.; Bornschein, Marcos R. [UNESP] (Pensoft Publishers, 2017)
The Japanese land snail Ovachlamys fulgens is reported for the first time in Brazil. We recorded the species in 2015 and 2017 in the municipalities of Santos and São Vicente in the metropolitan region of Baixada Santista, São Paulo state, southeastern Brazil. We found the species in an urban park and in a secondary forest altered by exotic plants. As this species is considered a pest and is capable of transmitting disease to humans, we propose that urgent measures be taken by the Brazilian government to control its populations.
Keywords: Atlantic Forest; Baixada Santista; Bioinvasion; Eosinophilic meningitis; Management of protected areas; Orchid seedlings